Method for effectively regulating and controlling iron circulation on surface of micron zero-valent iron and application

By mixing L-ascorbic acid 2-phosphate sesquimazide salt solution with zero-valent iron for modification reaction, the iron circulation of micron zero-valent iron surface is solved, and the surface of zero-valent iron materials is easily passivated and the iron circulation rate is slow when treating chromium-containing heavy metal wastewater, and the material's ability to efficiently remove hexavalent chromium is achieved.

CN119591231AActive Publication Date: 2025-03-11SHANDONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411769586.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

When treating chromium-containing heavy metal wastewater, existing zero-valent iron materials have problems such as easy passivation on the surface, slow iron circulation rate and low electron utilization rate, which limits their pollution removal performance.

Method used

By mixing L-ascorbic acid 2-phosphate magnesium sesquimolar salt solution with zero valence iron for modification reaction, the iron circulation on the surface of micron zero valence iron is regulated, and a modified micron zero valence iron material is prepared.

Benefits of technology

The specific surface area of ​​the modified micron zero-valent iron material has increased significantly, the iron element circulation has been promoted, and the reduction performance has been improved. It can quickly remove hexavalent chromium from water and significantly improve the removal efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591231A_ABST
    Figure CN119591231A_ABST
Patent Text Reader

Abstract

The invention relates to a method for effectively regulating and controlling iron circulation on the surface of micron zero-valent iron and application, micron zero-valent iron particles are modified by introducing L-ascorbic acid precursor L-ascorbic acid 2-phosphate sesquimagnesium salt, the reduction performance of zero-valent iron is remarkably improved, and iron substance circulation is promoted; and the chromium pollutants can be quickly removed by mechanically stirring for 10 minutes in an aerobic environment. The introduction of the L-ascorbic acid 2-phosphate magnesium sesquioxide can effectively regulate and control the iron circulation on the particle surface, improve the electron transfer efficiency, significantly improve the hydrophobicity of the material, and overcome the defects of easy passivation, low electron selectivity, slow surface iron circulation rate and the like of the traditional zero-valent iron. The modified micron zero-valent iron material is environmentally friendly, free of pollution, high in repeated utilization rate and high in electron utilization rate, and an innovative solution is provided for efficient treatment of chromium-containing industrial wastewater and other heavy metal wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental remediation, and relates to a method for successfully preparing a modified micron zero-valent iron material by regulating the iron cycle on the surface of zero-valent iron using L-ascorbic acid 2-phosphate sesquimagnesium salt, and applying the material to the treatment of chromium-containing heavy metal wastewater. Background Art

[0002] Hexavalent chromium (Cr(VI)) is a common and highly toxic pollutant in industrial wastewater and groundwater. It is highly soluble and mobile, and can spread rapidly in the environment, contaminating groundwater, soil and the food chain. It can cause cancer, respiratory diseases and skin ulcers through drinking water or skin contact. In addition, long-term exposure to low concentrations of hexavalent chromium can also cause chronic damage to the liver, kidneys and immune system, and even lead to gene mutations. Therefore, Cr(VI) is significantly harmful to the human body and the ecological environment. Zero-valent iron, as an environmentally friendly, inexpensive and readily available reducing substance, can reduce hexavalent chromium (Cr(VI)) to non-toxic trivalent chromium (Cr(III)). However, the disadvantages of zero-valent iron, such as easy passivation of the surface and low electron utilization, limit its practical application to a certain extent. Therefore, modifying zero-valent iron to improve its decontamination performance is currently a hot topic of concern for many researchers.

[0003] Zero-valent iron removes Cr(VI) mainly through adsorption, reduction and co-precipitation, among which the reduction effect is mainly attributed to the gradual release of Fe(II) by zero-valent iron in different ways (Equation 1-2). In addition, there is a Fe(III) / Fe(II) cycle on the surface of zero-valent iron (Equation 3) to ensure the continuous generation of Fe(II) and reduce the precipitation of iron during the reaction. Therefore, exploring efficient iron cycle regulation methods on the surface of zero-valent iron will help improve its reaction activity and achieve twice the result with half the effort in decontamination.

[0004] Fe 0 +2H + →Fe(II)+H2 (1)

[0005] 2Fe 0 +2H2O+O2→2Fe(II)+4OH - (2)

[0006] Fe 0 +2Fe(III)→3Fe(II) (3)

[0007] Chinese patent document CN202111043953.2 discloses a sulfurized modified micron zero-valent iron material and its preparation method and application, but the sulfurized modification process will produce harmful gas hydrogen sulfide and the material preparation time is long.

[0008] Zhou et al. used L-cysteine ​​to modify zero-valent iron using the ball milling method, which reduced the redox potential of the Fe(III) / Fe(II) cycle and promoted the Fe 0 Surface Fe(III) / Fe(II) cycle. However, the material preparation method is energy-intensive, the preparation process is too cumbersome and complicated, and the reusability is poor (J. Hazard. Mater, 2023, 456, 131717). Summary of the invention

[0009] In view of the above-mentioned status of the prior art, especially the problems of easy passivation of the zero-valent iron surface, slow iron circulation rate, low electron utilization rate, etc., the present invention uses L-ascorbic acid 2-phosphate sesquimagnesium salt to achieve effective regulation and modification of the iron circulation on the surface of micron zero-valent iron. The micron zero-valent iron material after regulation and modification can quickly remove hexavalent chromium in water.

[0010] Therefore, an object of the present invention is to provide a method for effectively regulating the iron cycle on the surface of micronized zero-valent iron.

[0011] The second object of the present invention is to provide a micron zero-valent iron material regulated and modified by the above method.

[0012] The third object of the present invention is to provide the use of the micron zero-valent iron material modified by the above method in the treatment of chromium-containing wastewater.

[0013] The technical solution for achieving the above-mentioned invention object can be summarized as follows:

[0014] A method for effectively regulating the iron cycle on the surface of micron zero-valent iron is provided, wherein a solution of L-ascorbic acid 2-phosphate sesquimagnesium salt is mixed with zero-valent iron for a modification reaction.

[0015] According to the present invention, a micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt is also provided, wherein the iron source is micron zero-valent iron, the modifier is L-ascorbic acid 2-phosphate sesquimagnesium salt, and the molar ratio of the iron source to the modifier is 1:(0.05-0.06), and most preferably 1:0.056.

[0016] According to the present invention, the method for preparing the micronized zero-valent iron material modified by the above-mentioned L-ascorbic acid 2-phosphate sesquimagnesium salt comprises the following steps:

[0017] The zero-valent iron is pickled with acetic acid-sodium acetate buffer in an anaerobic environment to remove the passivation layer on the surface, and then L-ascorbic acid 2-phosphate sesquimagnesium salt solution is added to react by oscillation. The suspension after the reaction is filtered and freeze-dried to obtain the micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt.

[0018] According to the present invention, preferably, the zero-valent iron is micron zero-valent iron, and the particle size is 70-80 μm.

[0019] According to the present invention, preferably, the pH of the acetic acid-sodium acetate buffer solution is 4, and the concentration is 0.2 mol / L.

[0020] According to the present invention, preferably, the concentration of L-ascorbic acid 2-phosphate sesquimagnesium salt solution is 0.1 mol / L.

[0021] According to the present invention, preferably, the molar ratio of zero-valent iron to L-ascorbic acid 2-phosphate sesquimagnesium salt is 1:(0.05-0.06), most preferably 1:0.056.

[0022] According to the present invention, preferably, the time for the micron zero-valent iron particles to oscillate and react in a buffer solution to remove the passivation film in an oxygen-free environment is 10 minutes.

[0023] According to the present invention, preferably, the oscillation reaction time is 10 h and the temperature is 25°C.

[0024] According to the present invention, the micronized zero-valent iron material modified by the above-mentioned L-ascorbic acid 2-phosphate sesquimagnesium salt is used in treating chromium-containing heavy metal wastewater.

[0025] According to the present invention, there is also provided a method for rapidly treating chromium-containing heavy metal wastewater, comprising the following steps:

[0026] The micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt is put into chromium-containing heavy metal wastewater, and the hexavalent chromium in the solution is quickly removed through mechanical stirring under an aerobic environment.

[0027] According to the present invention, preferably, the material of the stirring paddle used for mechanical stirring during the pollutant removal process is polytetrafluoroethylene, the rotation speed of the stirring paddle during mechanical stirring is 400±10r / min, and the hexavalent chromium pollutants can be completely removed within 10 minutes.

[0028] According to the present invention, preferably, the dosage of the micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt is 0.1-0.3 g / L, and most preferably 0.2 g / L.

[0029] According to the present invention, preferably, the reaction background solution for treating chromium-containing heavy metal wastewater is acetic acid-sodium acetate buffer, pH=5, and the solution concentration is 0.1-0.3 mol / L, most preferably 0.2 mol / L.

[0030] Beneficial effects of the present invention:

[0031] 1. The zero-valent iron particles (L-ZVI) modified by L-ascorbic acid 2-phosphate sesquimagnesium salt in the present invention have a significantly increased specific surface area compared to the unmodified zero-valent iron (ZVI), and the introduction of the modifier also promotes the circulation of iron elements on the surface of the particles, promotes the recycling and release of Fe(II), and improves its reduction performance.

[0032] 2. The zero-valent iron particles modified by L-ascorbic acid 2-phosphate sesquimagnesium salt in the present invention have greatly improved the ability to remove hexavalent chromium from water. Removal experiments were conducted on chromium-containing heavy metal wastewater, and it was found that the material only took 10 minutes to completely remove Cr(VI) in an acetic acid-sodium acetate buffer solution with a pH of 5, while the original micron zero-valent iron material took 180 minutes to achieve the same removal effect under the same conditions.

[0033] 3. The modifier L-ascorbic acid 2-phosphate sesquimagnesium salt of the present invention is safe and pollution-free and can be used as a food additive. It can regulate the interface of micron zero-valent iron particles, greatly improve the performance of zero-valent iron materials, and to a certain extent overcome the problems of easy passivation of zero-valent iron materials themselves, low electron selectivity, and slow surface iron circulation rate.

[0034] 4. The raw materials of the present invention are cheap, easily available, and environmentally friendly. The preparation process is simple and easy to operate. The modified zero-valent iron material has excellent decontamination performance and excellent reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an electron microscope scan of commercially purchased micronized zero-valent iron material;

[0036] Figure 2 This is an electron microscope scanning image of the micron zero-valent iron material whose surface has been regulated by iron circulation in Example 1;

[0037] Figure 3 This is an element mapping diagram of the micron zero-valent iron material whose surface has been regulated by iron cycle in Example 1;

[0038] Figure 4 This is the XPS (X-ray photoelectron spectroscopy) analysis chart of commercially purchased micron zero-valent iron material;

[0039] Figure 5 This is an XPS (X-ray photoelectron spectroscopy) analysis diagram of the modified micron zero-valent iron material whose surface has been regulated by iron cycle in Example 1;

[0040] Figure 6 It is a comparison of Tafel curves of commercially purchased micron zero-valent iron material (ZVI) and modified micron zero-valent iron material (L-ZVI) whose surface has been regulated by iron circulation;

[0041] Figure 7is a comparison diagram of the concentration change curve of the Cr(VI) removal process in Experimental Example 1;

[0042] Figure 8 This is a comparison chart of reaction rate constants of the pseudo-first-order kinetic reaction fitting of the Cr(VI) removal process in Experimental Example 1.

[0043] Fig. 9 It is a comparison chart of the concentration change curves of the reaction process of the cyclic experiment of the material of Example 1 in Experimental Example 2 and the commercial zero-valent iron material. DETAILED DESCRIPTION

[0044] The present invention pickles the micron zero-valent iron in an anaerobic environment to remove its surface passivation layer, then adds a modifier L-ascorbic acid 2-phosphate sesquimagnesium salt to synthesize the modified material L-ZVI, thereby achieving efficient regulation of the iron cycle on the surface of the zero-valent iron. The material is put into chromium-containing heavy metal wastewater, and hexavalent chromium pollutants in the water can be quickly removed by mechanical stirring under aerobic conditions. The introduction of L-ascorbic acid 2-phosphate sesquimagnesium salt can effectively regulate the iron cycle on the surface of micron zero-valent iron particles, improve its electron transfer efficiency, and significantly improve the hydrophobicity of the material, overcoming the shortcomings of traditional zero-valent iron such as easy passivation, low electron selectivity, and slow surface iron circulation rate.

[0045] The present invention provides a method for effectively regulating the iron circulation on the surface of micron zero-valent iron, which is to mix an L-ascorbic acid 2-phosphate sesquimagnesium salt solution with zero-valent iron for a modification reaction. L-ascorbic acid can reduce Fe(III) to Fe(II) due to its strong reducing property, but L-ascorbic acid itself is unstable and easily oxidized. Therefore, the present invention selects its precursor, i.e., the stable L-ascorbic acid 2-phosphate sesquimagnesium salt as a modifier to react with zero-valent iron to prepare a material. L-ascorbic acid 2-phosphate sesquimagnesium salt exists in various forms and can be used in the present invention in the form of L-ascorbic acid 2-phosphate sesquimagnesium salt hydrate.

[0046] The introduction of the above modifiers changes the structure of the passivation layer on the surface of the micron zero-valent iron particles and promotes the circulation of iron substances on the surface. In addition, the reducibility of the modified micron zero-valent iron is greatly improved, the electron transfer rate is accelerated, and the chromium pollutants can be quickly removed by mechanical stirring for 10 minutes in an aerobic environment.

[0047] According to the present invention, the micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt, the iron source is micron zero-valent iron, and the modifier is L-ascorbic acid 2-phosphate sesquimagnesium salt.

[0048] In one or more preferred embodiments, the molar ratio of the iron source to the modifier is 1:(0.05-0.06), most preferably 1:0.056.

[0049] According to the present invention, the method for preparing the micronized zero-valent iron material modified by the above-mentioned L-ascorbic acid 2-phosphate sesquimagnesium salt comprises the following steps:

[0050] The zero-valent iron is washed with acetic acid-sodium acetate buffer in an oxygen-free environment to remove the passivation layer on the surface, and then L-ascorbic acid 2-phosphate sesquimagnesium salt solution is added for oscillation reaction. The suspension after the reaction is filtered and freeze-dried to obtain the micron zero-valent iron material regulated and modified by L-ascorbic acid 2-phosphate sesquimagnesium salt. It can be sealed and stored in a vacuum bag.

[0051] In one or more preferred embodiments, the zero-valent iron is micron zero-valent iron, and the particle size is 70-80 μm.

[0052] In one or more preferred embodiments, the pH of the acetic acid-sodium acetate buffer solution is 4, and the concentration is 0.2 mol / L.

[0053] In one or more preferred embodiments, the concentration of the L-ascorbic acid 2-phosphate sesquimagnesium salt solution is 0.1 mol / L.

[0054] In one or more preferred embodiments, the molar ratio of zero-valent iron to L-ascorbic acid 2-phosphate sesquimagnesium salt is 1:(0.05-0.06), most preferably 1:0.056.

[0055] In one or more preferred embodiments, the time for removing the passivation film by oscillating the micron zero-valent iron particles in the buffer solution in an oxygen-free environment is 10 minutes.

[0056] In one or more preferred embodiments, the shaking reaction time is 10 h and the temperature is 25°C.

[0057] According to the present invention, the micronized zero-valent iron material modified by the above-mentioned L-ascorbic acid 2-phosphate sesquimagnesium salt is used in treating chromium-containing heavy metal wastewater.

[0058] According to the present invention, there is also provided a method for rapidly treating chromium-containing heavy metal wastewater, comprising the following steps:

[0059] The micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt is put into chromium-containing heavy metal wastewater, and the hexavalent chromium in the solution is quickly removed through mechanical stirring under an aerobic environment.

[0060] In one or more preferred embodiments, the material of the stirring paddle used for mechanical stirring during the pollutant removal process is polytetrafluoroethylene, and the rotation speed of the stirring paddle during mechanical stirring is 400±10r / min, and the hexavalent chromium pollutants can be completely removed within 10 minutes.

[0061] In one or more preferred embodiments, the dosage of the modified micron zero-valent iron material regulated by L-ascorbic acid 2-phosphate sesquimagnesium salt is 0.1-0.3 g / L, most preferably 0.2 g / L.

[0062] In one or more preferred embodiments, the reaction background solution for treating chromium-containing heavy metal wastewater is acetic acid-sodium acetate buffer, pH=5, and the solution concentration is 0.1-0.3 mol / L, most preferably 0.2 mol / L.

[0063] In one or more preferred embodiments, the modified micron zero-valent iron material is used to treat chromium-containing heavy metal wastewater, and the Cr(VI) concentration of the chromium-containing wastewater is 5 mg / L.

[0064] The present invention is further described below by means of specific embodiments and drawings, but is not limited thereto.

[0065] Example 1

[0066] The preparation method of the micronized zero-valent iron material with iron cycle regulated by L-ascorbic acid 2-phosphate sesquimagnesium salt is as follows:

[0067] A 250ml volumetric flask was used to prepare an acetic acid-sodium acetate buffer solution with a pH of 4 and a concentration of 0.2mol / L, and then it was transferred to a 250ml serum bottle, and nitrogen was continuously filled into the bottle until the reading of the dissolved oxygen meter showed 0 (about 30min), 1g of iron powder was weighed and added to the bottle, and the bottle mouth was quickly sealed with a rubber stopper, and the sealed serum bottle was placed in a flip-type oscillator with a speed of 120r / min and an ambient temperature of 25±1°C for 10min of reaction, and the surface passivation layer was initially removed by acid washing, and the serum bottle was taken out after 10min, and 10ml of the prepared L-ascorbic acid 2-phosphate sesquimagnesium salt solution with a concentration of 0.1mol / L was quickly drawn with a 10ml syringe, and injected into the serum bottle through the rubber stopper of the bottle mouth, and then the serum bottle was immediately placed in the flip-type oscillator again to continue the reaction for 10h. The suspension after the reaction was completed was filtered, and the material was placed in a vacuum drying oven for freeze drying for 2h, and after drying, it was placed in a vacuum bag and sealed for storage.

[0068] The electron microscope scanning image of the commercially purchased micron zero-valent iron material is shown in the figure below. Figure 1 As shown, the electron microscope scanning image of the micron zero-valent iron material whose surface has been regulated by iron circulation in this embodiment is as follows Figure 2 As shown. Figure 1 , Figure 2It can be seen that compared with the relatively smooth surface of the commercially purchased micron zero-valent iron material, the surface of the modified material in Example 1 is relatively rough, with obvious pores and cracks. This porous microstructure provides more active reaction sites, which helps to increase the specific surface area, thereby improving the mass transfer efficiency between the reactants and accelerating the reaction rate.

[0069] The molar ratio of the iron source to the modifier L-ascorbic acid 2-phosphate sesquimagnesium salt in this embodiment is 1:0.056. The mapping diagram of the elements contained in the modified material is as follows: Figure 3 shown.

[0070] The XPS images of the commercially available micron zero-valent iron material and the modified material of this embodiment are shown in FIG. Figure 4-5 As shown. Figure 4 , Figure 5 It can be seen that although the types of elements on the particle surface have not changed, a comparison between the two shows that compared with the commercially purchased micron zero-valent iron material (ZVI, Fe(II) accounts for 24.53%), the Fe(II) content on the surface of the modified particles has increased to 49.20%, and the corresponding Fe(III) content has decreased from 75.47% to 50.8%. The increase in the proportion of divalent iron has improved the reducibility of the modified material.

[0071] The comparison of Tafel curves of commercially available micron zero-valent iron material (ZVI) and modified micron zero-valent iron material (L-ZVI) with iron cycle regulation on the surface of this embodiment is shown in the figure. Figure 6 As shown. Figure 6 It can be seen that L-ZVI (-0.962V) has a more negative corrosion potential than ZVI (-0.92V), and L-ZVI exhibits a higher current density and a significantly negatively shifted peak potential during the reduction process, indicating that L-ZVI has a superior electron transfer ability and significantly improved electrochemical activity.

[0072] Example 2

[0073] The material prepared in Example 1 was used to treat heavy metal wastewater containing chromium. The concentration of the chromium-containing wastewater to be treated was 5 mg / L, and the reaction background solution was an acetic acid-sodium acetate buffer solution with a pH of 5.

[0074] The specific steps are as follows:

[0075] Transfer 500 ml of the prepared acetic acid-sodium acetate buffer solution to a 500 ml beaker, add 1 ml of chromium stock solution (concentration of 2500 mg / L) to make the chromium concentration of the reaction system 5 mg / L, then weigh 0.1 g of the modified material and add it to the beaker to start the reaction. Mechanical stirring is carried out in an aerobic environment at a speed of 400±10 r / min. The removal rate of Cr(VI) can reach 100% within 10 minutes of reaction.

[0076] Example 3

[0077] As described in Example 1, except that:

[0078] The molar ratio of the iron source to the modifier L-ascorbic acid 2-phosphate sesquimagnesium salt is 1:0.05.

[0079] Example 4

[0080] As described in Example 1, except that:

[0081] The molar ratio of the iron source to the modifier L-ascorbic acid 2-phosphate sesquimagnesium salt is 1:0.06.

[0082] Comparative Example 1

[0083] As described in Example 1, the difference is that after the zero-valent iron is pickled for 10 minutes, a sodium sulfide solution is added to continue the reaction for 10 hours, and the molar ratio of iron to sulfur is 1:0.056 to obtain the material.

[0084] Comparative Example 2

[0085] As described in Example 1, except that after the zero-valent iron was pickled for 10 minutes, L ascorbic acid solution was added to continue the reaction for 10 hours, and the molar ratio of L ascorbic acid to iron source was 0.056:1.

[0086] Test Example 1

[0087] The process curves of treating chromium-containing wastewater by Example 1, commercially purchased micron zero-valent iron materials, and the materials prepared in Comparative Examples 1-2 are plotted, as shown in FIG. Figure 7-8 shown.

[0088] Depend on Figure 7-8It can be seen that the materials used in Example 1 and Comparative Example 1 show significantly better degradation performance than the commercially purchased micron zero-valent iron materials and the materials of Comparative Example 2. In particular, in the first 20 minutes, the target pollutant Cr(VI) of Example 1 and Comparative Example 1 is rapidly degraded to near zero, showing a high reaction rate and efficiency, while the removal rates of the commercially purchased micron zero-valent iron materials and the materials of Comparative Example 2 within 20 minutes are only 10% and 60%, respectively. This is attributed to the modification of the materials in Example 1 and Comparative Example 1 to enhance the reaction activity. In addition, the pollutant concentration at each time point in Example 1 is lower than that in Comparative Example 1, and the pollutants are completely removed in the shortest time (10 minutes), indicating that the reaction activity of Example 1 is higher than that of Comparative Example 1, and no harmful gases such as hydrogen sulfide are produced compared with it, reflecting the significant advantages of the present invention.

[0089] Test Example 2

[0090] The material in Example 1 was used to carry out a cycle experiment, and a commercially purchased micron zero-valent iron material was used as a comparison. The specific operation steps are as follows:

[0091] 500 ml of the prepared acetic acid-sodium acetate buffer solution with a pH of 5 was transferred to a beaker, and a chromium stock solution was added to make its pollutant concentration 5 mg / L. The mechanical stirring paddle was turned on, and 0.1 g of the modified new material (L-ZVI) in Example 1 was added to start the experiment. When the chromium pollutant in the solution was completely removed (within 10 min), Cr (VI) was repeatedly added to evaluate the reusability of L-ZVI. The experiment was stopped after 5 cycles (480 min).

[0092] A commercially available micronized zero-valent iron material (ZVI) was used as a comparison. The operation process was the same as the modified new material (L-ZVI) in Example 1, and the experiment was stopped at 480 minutes.

[0093] The comparison of pollutant concentration change curves during the cycle experiment of this embodiment is as follows: Fig. 9 As shown by Fig. 9 It can be seen that L-ZVI in Example 1 performed 5 complete cycles within 480 minutes and still had a continuous removal ability and was highly reusable. In contrast, the commercially purchased micron zero-valent iron material only performed less than 3 cycles within the same time and had a slow reaction rate.

Claims

1. A method for effectively regulating the iron circulation on the surface of micron zero-valent iron, characterized in that: The method comprises the following steps: mixing L-ascorbic acid 2-phosphate sesquimagnesium salt solution with zero-valent iron to carry out a modification reaction.

2. A micronized zero-valent iron material regulated and modified by L-ascorbic acid 2-phosphate sesquimagnesium salt, characterized in that the iron source is micronized zero-valent iron, the modifier is L-ascorbic acid 2-phosphate sesquimagnesium salt, and the molar ratio of the iron source to the modifier is 1:(0.05-0.06).

3. The method for preparing the micronized zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt according to claim 2 comprises the following steps: The zero-valent iron is pickled with acetic acid-sodium acetate buffer in an anaerobic environment to remove the passivation layer on the surface, and then L-ascorbic acid 2-phosphate sesquimagnesium salt solution is added for oscillation reaction. The suspension after the reaction is filtered and freeze-dried to obtain the micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt.

4. The method for preparing the micronized zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt according to claim 3, characterized in that: The zero-valent iron is micron zero-valent iron, and the particle size is 70-80 μm.

5. The method for preparing the micronized zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt according to claim 3, characterized in that: The pH of the acetic acid-sodium acetate buffer solution is 4, and the concentration is 0.2 mol / L.

6. The method for preparing the micronized zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt according to claim 3, characterized in that: The molar ratio of zero-valent iron to L-ascorbic acid 2-phosphate sesquimagnesium salt is 1:(0.05-0.06); Preferably, the time for the micron zero-valent iron particles to oscillate in a buffer solution to remove the passivation film in an oxygen-free environment is 10 minutes; the oscillation reaction time is 10 hours, and the temperature is 25°C.

7. Use of the micronized zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt as claimed in claim 2 in treating chromium-containing heavy metal wastewater.

8. A method for rapidly treating chromium-containing heavy metal wastewater, comprising using the micronized zero-valent iron material modified by the L-ascorbic acid 2-phosphate sesquimagnesium salt of claim 2, comprising the following steps: The micron zero-valent iron material modified by L-ascorbic acid 2-phosphate sesquimagnesium salt is put into chromium-containing heavy metal wastewater, and the hexavalent chromium in the solution is quickly removed through mechanical stirring under an aerobic environment.

9. The method for rapidly treating chromium-containing heavy metal wastewater according to claim 8, characterized in that: The dosage of the modified micron zero-valent iron material regulated by L-ascorbic acid 2-phosphate sesquimagnesium salt is 0.1-0.3g / L.

10. The method for rapidly treating chromium-containing heavy metal wastewater according to claim 8, characterized in that: The reaction background solution for treating chromium-containing heavy metal wastewater is acetic acid-sodium acetate buffer solution, pH=5, and the solution concentration is 0.1-0.3 mol / L.

Citation Information

Patent Citations

  • Vulcanization modified micron zero-valent iron material as well as preparation method and application thereof

    CN115771941A

  • Method for improving zero-valent iron dechromisation catalytic reduction liveness in neutrality condition

    CN101244864A

  • Fluorescence biosensor, and preparation method and purpose thereof

    CN106483110A

  • Method for removing organic pollutants by activating hydrogen peroxide with small molecular acid reinforced zero-valent iron

    CN115677013A

  • Function material, filter, composition for cosmetic raw material and food additive, and manufacturing method for functional material

    JP2006081971A